The Reveal of the Financial Investment, which Affect the Adultery Decision in the Commercial Banks (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The recent research aims to clarity the impact of financial accounting diminution and never shows that up obviously. It considers one of the most difficult concerns to make the right decision about. The research has mainly focused upon the accounting analysis of the financial lists that to Baghdad bank investment between (2014- 2007). This research reached to many actual applied results like unexposed accountancy numbers, which make the process harder to get the right decision